The Anomalous Magnetic Field of “Kaprovani” Settlement Territory and its Geological Interpretation - Gogua, Robert A.; Kiria, Jemal K.; Ghlonti, Nugzar Ya. (Journals of Georgian Geophysical Society, 2022)
As a result of the geomagnetic studies conducted on the territory of Kaprovani we determined the magnetic absorption intensity of the anomalous magnetic field and the sand of the territory, percentage of ferromagnetic minerals in the sand and the source of the anomalous magnetic field.